Biologia populacional e reprodutiva de Callinectes danae Smith (Crustacea, Portunidae), no Balneário Shangri-lá, Pontal do Paraná, Paraná, Brasil - Baptista-Metri, Cassiana; Pinheiro, Marcelo A. A. [UNESP]; Blankensteyn, Arno; Borzone, Carlos A. (Sociedade Brasileira de Zoologia, 2005)
Entre abril/2000 a abril/2001 todos os indivíduos de C. danae Smith, 1869 procedentes de um mesmo arrasto foram coletados em visitas quinzenais às bancas dos pescadores do Balneário Shangri-lá (25°37'30S, 48°25'08W) visando investigar sua estrutura populacional e parâmetros reprodutivos. de cada indivíduo foi determinado o sexo, a largura cefalotorácica (LC) e o peso úmido (P). O estágio de maturação gonadal foi determinado macroscopicamente pelo aspecto e coloração das gônadas. A massa de ovos das fêmeas foi separada para análise da fecundidade. Foi observado um predomínio de fêmeas adultas (incluindo as ovígeras) em relação às outras categorias. A proporção sexual foi 0,9:1 (machos:fêmeas). O tamanho de primeira maturação sexual foi estimado em 60,5 mm (machos) e 52,7 mm (fêmeas). A relação LC/P foi isométrica para machos e fêmeas. A largura da carapaça das fêmeas ovígeras variou de 43,2 a 79,5 mm (67 ± 8 mm), com fecundidade variando entre 25.127 e 246.676 ovos, com uma média de 127.177 ovos por fêmea. O diâmetro médio dos ovos foi de 0,22 mm. A maior incidência de fêmeas ovígeras ocorreu durante o inverno e o verão.

From April 2000 to April 2001 all individuals of C. danae Smith, 1869 included on one otter-trawl by-catch was fortnightly sampled at Shangri-lá's fish market (25°37'30S, 48°25'08W) in order to study their population structure and reproductive pattern. Each specimen was sexed and measured (CW = carapace width, excluding lateral spines; WW = wet weight). The gonadal maturation stage was determined macroscopically based on its color and size. The egg mass of the females was separate for fecundity analysis. Prevalence of adult females (including ovigerous ones) was observed comparing to other categories. Sexual proportion was 0.9:1 (males:females). Size at first sexual maturation was estimated at 60.5 mm for males, and 52.7 mm for females. WW/WC relationship was isometric for males and females. The carapace width of ovigerous females was between 43.2 to 79.5 mm (67 ± 8 mm), and fecundity varied from 25,127 to 246,676 eggs, with an average of 127,177 eggs per female and mean egg diameter was 0.22 mm. The highest presence of ovigerous females occurred during winter and summer.
Populational and reproductive biology of C. danae Smith, (Crustacea, Portunidae) in Shangri-lá Beach, Pontal do Paraná, Paraná, Brazil
Keywords: Fecundidade; biologia populacional; fauna acompanhante; razão sexual; siris; Fecundity; population biology; seabob by-catch; Sex-ratio; swimming crab